Paolo Mastrocola, Luca Ricolfi, Il danno scolastico. La scuola progressiva come macchina della disuguaglianza. (Altre Modernità, 2022)
Paolo Mastrocola, Luca Ricolfi, Il danno scolastico. La scuola progressiva come macchina della disuguaglianza. (Milano, La Nave di Teseo, 2021, 272 pp. ISBN 883-460-469-5)di Alfonso D’ambrosio